A case of tacrolimus-induced supraventricular arrhythmia after kidney transplantation - Kim, Bo-Ra (2013)
CONTEXT: Tacrolimus is a potent immunosuppressive drug often administered to transplant recipient patients and exhibits a variety of adverse cardiovascular effects. CASE REPORT: We report a case of a 53-year-old Asian female who developed various arrhythmic phenomena including atrial premature complexes and supraventricular tachycardia after administration of tacrolimus. CONCLUSION: Tacrolimus-associated arrhythmia after kidney transplantation may be life-threatening, and so patients undergoing this procedure should be carefully monitored.